2023
DOI: 10.1007/jhep06(2023)088
|View full text |Cite
|
Sign up to set email alerts
|

To Half-Be or Not To Be?

Abstract: It has recently been argued that half degrees of freedom could emerge in Lorentz and parity invariant field theories, using a non-linear Proca field theory dubbed Proca-Nuevo as a specific example. We provide two proofs, using the Lagrangian and Hamiltonian pictures, that the theory possesses a pair of second class constraints, leaving D − 1 degrees of freedom in D spacetime dimensions, as befits a consistent Proca model. Our proofs are explicit and straightforward in two dimensions and we discuss how they gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 97 publications
0
1
0
Order By: Relevance
“…In particular, they exhibit hot Big Bang solutions featuring a late-time self-accelerating epoch, and additionally at the perturbative level certain sub-classes of the theory satisfy all stability and subluminality conditions, and intriguingly, gravitational waves propagate at the speed of light. Moreover, further cosmological solutions of the theory have been studied in [77], while the complete analysis of the constraint algebra has been performed in [78,79]. Finally, the quantum stability of Proca-Nuevo interactions was explored in [80], where it was found that Proca-Nuevo and generalized Proca theories have analogous behaviour at the quantum level, opening the door to speculations for being specific cases of a more general theory.…”
Section: Jcap04(2024)051mentioning
confidence: 99%
“…In particular, they exhibit hot Big Bang solutions featuring a late-time self-accelerating epoch, and additionally at the perturbative level certain sub-classes of the theory satisfy all stability and subluminality conditions, and intriguingly, gravitational waves propagate at the speed of light. Moreover, further cosmological solutions of the theory have been studied in [77], while the complete analysis of the constraint algebra has been performed in [78,79]. Finally, the quantum stability of Proca-Nuevo interactions was explored in [80], where it was found that Proca-Nuevo and generalized Proca theories have analogous behaviour at the quantum level, opening the door to speculations for being specific cases of a more general theory.…”
Section: Jcap04(2024)051mentioning
confidence: 99%